2008
DOI: 10.1136/hrt.2007.125708
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a disease management programme for secondary prevention of coronary heart disease and heart failure in primary care

Abstract: The use of a nurse-led disease management programme is associated with increased costs in other coronary heart disease-related services as well as for the costs of the clinics. They are also associated with improvements in health. Even in the short term these disease management programmes may represent a cost-effective service, as additional QALY are generated at an acceptable extra cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…Whether a DMP is a cost-effective way to manage these patients is not well established. The studies suggest a DMP may be cost effective or the extra cost associated with a DMP is acceptable (131,(139)(140)(141)(142). In a recent analysis by Whellan et al (143), an interesting concept based on the American system of reimbursement is presented.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
“…Whether a DMP is a cost-effective way to manage these patients is not well established. The studies suggest a DMP may be cost effective or the extra cost associated with a DMP is acceptable (131,(139)(140)(141)(142). In a recent analysis by Whellan et al (143), an interesting concept based on the American system of reimbursement is presented.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
“…They add further weight to the assertion that disease management programmes delivered in primary care may be a cost effective alternative to existing care for patients with existing coronary heart disease [31][32][33]. The gains associated with the intervention were predominantly driven by reductions in costs rather than improvements in effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Several nurse-led intervention programs focused on patients younger than 65 years or were tailored to patients with heart failure so that the generalization to higher age groups or to patients discharged after an acute cardiac event cannot be ensured. For patients with CHD, there is only one study on cost-effectiveness with a follow-up period of 4 years [14] and two studies covering a period of 1 year [15,16]. In the 4-year follow-up study, Raftery et al [14] observed no differences in costs but differences in QALYs (þ0.124 QALYs; ICER €1590/QALY).…”
Section: Discussionmentioning
confidence: 97%
“…There are only three studies that performed a formal cost-effectiveness analysis for patients with CHD [14][15][16] and five studies that performed an analysis for patients with heart failure [17][18][19][20][21] estimating cost per QALY with different results.…”
Section: Introductionmentioning
confidence: 99%